2008
DOI: 10.1002/jmri.21218
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the thorax during whole‐body MRI: Evaluation of different MR sequences and comparison to thoracic multidetector computed tomography (MDCT)

Abstract: Purpose:To evaluate the accuracy of four MR sequences used as part of a whole-body MRI protocol to detect pulmonary lesions in cancer patients. Materials and Methods:A total of 31 oncology patients were imaged in a 1.5T MR scanner (Magnetom Avanto; Siemens Medical Solutions, Germany) for whole-body staging. MR chest imaging included: axial and coronal T2-weighted (T2w)-short-tau inversion-recovery (STIR), axial T2w turbo spin-echo (TSE), and contrast-enhanced (CE) three-dimensional (3D) volumetric interpolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 24 publications
5
42
0
2
Order By: Relevance
“…However, these lesions were very small in size (<4 mm), only just visible by WB-MRI, showed partial calcification in CT as well as absent FDG uptake on PET and therefore were difficult to interpret. Limited assessment and impaired diagnostic accuracy of lung nodules below 6 mm in both CT (69%) or MRI (43%) and a reduced sensitivity of PET for small-sized lung lesions has been previously described in the literature [30][31][32]. As a result of breathing-induced movement of lung parenchyma and depending on the resolution of the PET component, FDG activity can often be underestimated in small lung metastases or show no uptake at all.…”
Section: Discussionmentioning
confidence: 90%
“…However, these lesions were very small in size (<4 mm), only just visible by WB-MRI, showed partial calcification in CT as well as absent FDG uptake on PET and therefore were difficult to interpret. Limited assessment and impaired diagnostic accuracy of lung nodules below 6 mm in both CT (69%) or MRI (43%) and a reduced sensitivity of PET for small-sized lung lesions has been previously described in the literature [30][31][32]. As a result of breathing-induced movement of lung parenchyma and depending on the resolution of the PET component, FDG activity can often be underestimated in small lung metastases or show no uptake at all.…”
Section: Discussionmentioning
confidence: 90%
“…The detection rates or sensitivities of MR imaging using various sequences on 1.5 and 3.0 T systems have ranged from 36.0 to 96.0% (Kersjes et al 1997;Vogt et al 2004;Schroeder et al 2005;Luboldt et al 2006;Bruegel et al 2007;Regier et al 2007;Yi et al 2007;Frericks et al 2008;Koyama et al 2008;Sommer et al 2014). The study with 150 subjects considering as the large population to date compared CT and MR imaging on a 1.5 T system demonstrated that the overall detection rate of thin-section CT (97%) was superior to that of respiratory-triggered STIR turbo SE imaging (82.5%), although there were no significant differences between the methods in the detection rate for all types of malignant nodules (Koyama et al 2008).…”
Section: Detection Of Pulmonary Nodulesmentioning
confidence: 97%
“…In part, this was based on the practical consideration that the required sample size would be unachievable. In addition, although there was an a priori belief among the nodules, but smaller lesions (, 10 mm in diameter) may go undetected (15,29). Similarly, prior reports in patients with lymphoma have shown that sensitivity with whole-body MR imaging is 92%-100% for detecting nodes between 10 and 12 mm in diameter, versus a sensitivity of 67% for nodes between 6 and 12 mm in diameter and 11% for nodes between 1 and 6 mm in diameter (28,30).…”
Section: Pediatric Imaging: Whole-body Mr Imaging For Staging Of Pedimentioning
confidence: 97%